If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6 = 14 + -25 Reorder the terms: -6 + 2x = 14 + -25 Combine like terms: 14 + -25 = -11 -6 + 2x = -11 Solving -6 + 2x = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2x = -11 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = -11 + 6 2x = -11 + 6 Combine like terms: -11 + 6 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5
| -191.06=4.1(1-7b) | | 10+7x=-1x+106 | | 6h+7=30 | | 6x-18=3x-2 | | 2x+1+2x+2=12 | | 6-2(4x+3)+(x-5)=3-4(2x+3) | | (x-(4-5i))(x-(4+5i))=0 | | 5=9x+5 | | m=-12+n | | 15x^7/40x^9 | | Y^2+25=10v | | 3(x+2)+2(x+4)=4x+29 | | 68=5r-7 | | 2/3x-4=32 | | 8n^2-14n-9=0 | | 11x-4-6x=6x-3 | | 75=-4n+3 | | (x^2-10)=(x+2) | | 12=24x | | 4x-1=12/5 | | 109=1-4(1+4n) | | 2x+y=23754 | | 1.2(3-x)+7=4.6 | | ln(x^2-10)=ln(x+2) | | Q=1300-140P | | 5x-7y=-6 | | -4.5=x+2(4-3x) | | -6x+2=30+x | | u-6.6=4.36 | | 6r-12=-2r+36 | | y=2-7x | | -4x+3(x-1)=6 |